Kecemasan pada atlet bola voli di Surabaya: Bagaimana peranan mental toughness dan kohesivitas? - Armadi, Amaraditha Oktovia; Rini, Amanda Pasca; Saragih, Sahat (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2023)
This study aims to determine the relationship between mental toughness and cohesiveness with anxiety in volleyball athletes in Surabaya when facing matches. This study has three hypotheses, which contain: 1) there is a positive relationship between mental toughness and cohesiveness with anxiety; 2) there is a positive relationship between mental toughness and anxiety; 3) There is a positive relationship between cohesiveness and anxiety. This research is quantitative research using correlational research. Data collection was carried out for seven days through the distribution of online mental toughness, cohesivity, and anxiety scale questionnaires to volleyball athletes in Surabaya as many as 160 respondents. The data analysis used was multiple regression analysis with the help of SPSS 26. The results of this study showed 1) There is a positive relationship between mental toughness and cohesiveness with anxiety; 2) There is a positive relationship between mental toughness and anxiety. This means that the higher the mental toughness, the lower the anxiety; 3) There was no positive relationship between cohesiveness and anxiety. That is, high or low cohesiveness does not affect the high or low of anxiety. Therefore, the first and second hypotheses in this study are accepted, while the third hypothesis is not accepted. Penelitian ini bertujuan untuk mengetahui hubungan antara mental toughness dan kohesivitas dengan kecemasan pada atlet bola voli di Surabaya pada saat menghadapi pertandingan. Penelitian ini memiliki tiga hipotesis, yang berisi : 1) terdapat hubungan positif antara mental toughness dan kohesivitas dengan kecemasan; 2) terdapat hubungan positif antara mental toughness dengan kecemasan; 3) terdapat hubungan positif antara kohesivitas dengan kecemasan. Penelitian ini merupakan penelitian kuantitatif dengan menggunakan penelitian korelasional. Pengambilan data dilakukan selama tujuh hari melalui penyebaran kuesioner skala mental toughness, kohesivitas, dan kecemasan secara online kepada atlet bola voli di Surabaya sebanyak 160 responden. Analisis data yang digunakan adalah analisis regresi berganda dengan bantuan SPSS 26. Hasil dari penelitian ini menunjukkan 1) Adanya hubungan positif antara mental toughness dan kohesivitas dengan kecemasan; 2) Adanya hubungan positif antara mental toughness dengan kecemasan. Artinya semakin tinggi mental toughness maka semakin rendah kecemasan; 3) Tidak terdapat hubungan positif antara kohesivitas dengan kecemasan. Artinya tinggi atau rendahnya kohesivitas tidak mempengaruhi tinggi atau rendahnya kecemasan. Oleh karena itu, hipotesis pertama dan kedua pada penelitian ini diterima, sedangkan hipotesis ketiga tidak diterima.